Thyroid disorder in antenatal women in sub-himalayan region: a need for universal screening - Dubey, Swati; Pradhan, Anup (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thyroid dysfunction constitutes the second most common endocrine disorder of pregnancy, associated with adverse maternal and fetal outcome and is often overlooked in pregnancy due to their nonspecific symptoms and the hypermetabolic pregnant state. Objective of present study was to establish the prevalence of thyroid dysfunction, study the effects in pregnancy in sub-himalayan population and whether universal screening for thyroid dysfunction is required. Methods: The study was conducted on 200 patients in the age group of 20 to 35 years with a singleton pregnancy and gestational age between 6 to 24 weeks. Results: In the 200 women screened, the prevalence of thyroid dysfunction was found to be 14% with 8% having subclinical hypothyroidism while an equal percentage of 2% having clinical hypothyroidism, subclinical hyperthyroidism and clinical hyperthyroidism. The mean age of patients with subclinical hypothyroidism was 28.6 ± 4.9 years, with thyroid disorder in pregnancy being significantly more common in primigravida. Statistically significant association was found between patients with thyroid dysfunction and abortions, preeclampsia, preterm labor, small for gestational age, low birth weight, and admission to NICU. Conclusions: Prevalence of thyroid dysfunction was found to be high in our study, particularly subclinical hypothyroidism and was associated with adverse pregnancy outcomes; hence, more research is required in the Sub-Himalayan goitre belt to assess the magnitude of the problem and formulate universal screening protocols in this particular subset of the Indian population accordingly.